ANALISIS DAMPAK EKONOMI PENUTUPAN KAWASAN LOKALISASI KOTA SURABAYA ( Studi Deskriptif Dampak Ekonomi Penutupan Lokalisasi Dolly bagi masyarakat di Kelurahan Putat Jaya Kota Surabaya ) - Dedi Isnandar (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2015)
This research is the economic impact of the closure of Dolly the city of Surabaya. This study takes the title: "Economic Impact Analysis Closing Localization Region Surabaya (Descriptive Study Economic Impact of Closure Localization Dolly for Communities in Sub Putat Jaya Surabaya)". In this study aims to analyze and find out about the economic impact of the closure of the Localization Dolly for the community in the Village Putat Jaya Surabaya. Based on the formulation of the problem and the purpose of the existing research, this research is included in a descriptive qualitative research. In this study withdrawal sampling technique used was purposive sampling. The focus of research is seen from the dimensions of the economic impact in terms of three groups: Group business unit Local, Local labor groups, and local communities. The results of this research is in the area of Dolly impact on group business units locally decreased from income of units of local business, employment and no effect on the tax paid to the Local Government City of Surabaya today, the group of local workforce affected are reviewed of the workforce at the site, the number of working hours remain the same and wages did not rise that is different from the situation before localization is closed, the proportion of daily expenditure is now operating in the region has increased over wages did not rise, the working conditions under normal conditions and not normal (post-closing) business unit at this time is different because there is no additional work from the workers to get bonuses beyond the wages of individual business units - each. At the local communities lack the cash receipts for any Neighborhood or Rukun Warga current, formerly of the inclusion of the homeless - homeless Localization Dolly.